The Urgency of Curriculum Innovation: Implementation of the Independent Learning Curriculum at SMPN 4 Cikarang Utara in Bekasi - Wahyudin Wahyudin; Qiqi Yuliati Zaqiah; Bambang Qomaruzzaman (Universitas Muhammadiyah Enrekang, 2023)
This study describes innovation in the field of curriculum and implementation of the Independent Curriculum at SMPN 4 Cikarang Utara Bekasi. This study used a descriptive qualitative method, reinforced by library research. The author collects and analyzes data using articles, journals, and references related to the problem under study. Also, conducting surveys and interviews with educators and education staff who have practiced the Independent curriculum in schools.The results of this study indicate that the independent curriculum exists to answer the challenges of a dynamic era. Its manifestation is that it must support critical thinking skills in solving problems, have a creative and innovative spirit, and have 21st century communication and collaboration skills and be ready to welcome the Golden Era of 2045. An independent curriculum, makes educators creative in compiling teaching modules, so that they are able to teach students who have a strong character based on the Pancasila Student Profile with competencies to optimally strengthen character, literacy, and numeracy.